Habitat characteristics provide insights of carbon storage in seagrass meadows - Mazarrasa, Inés (2018)
Seagrass meadows provide multiple ecosystem services, yet they are among the most threatened ecosystems on earth. Because of their role as carbon sinks, protection and restoration of seagrass meadows contribute to climate change mitigation. Blue Carbon strategies aim to enhance CO2 sequestration and avoid greenhouse gasses emissions through the management of coastal vegetated ecosystems, including seagrass meadows. The implementation of Blue Carbon strategies requires a good understanding of the habitat characteristics that influence Corg sequestration. Here, we review the existing knowledge on Blue Carbon research in seagrass meadows to identify the key habitat characteristics that influence Corg sequestration in seagrass meadows, those factors that threaten this function and those with unclear effects. We demonstrate that not all seagrass habitats have the same potential, identify research priorities and describe the implications of the results found for the implementation and development of efficient Blue Carbon strategies based on seagrass meadows.